Strengthening Pancasila Leadership Character through the “Desa Bahagia” System: The Case of the Paskibraka Training Programme - Vijayanti Octavia, Devi; Syarief Nurdin, Encep; Ruyadi, Yadi (IJORER : International Journal of Recent Educational Research, 2025)
This study aims to evaluate the integration of the “Desa Bahagia” system as a character education framework in the Paskibraka national youth leadership training programme, with the goal of strengthening Pancasila-based leadership character. Employing a qualitative case study approach, data were collected through in-depth interviews with trainers, alumni, and coordinators, participatory observation during training sessions, and document analysis of programme curricula and reports. Thematic analysis was applied to interpret the data. Findings reveal that the “Desa Bahagia” System, which emphasizes holistic development (physical, mental, emotional), effectively fosters leadership traits aligned with Pancasila values, including discipline, cooperation, and social responsibility. However, regional disparities in implementation such as inconsistent trainer expertise and facility quality create challenges in achieving nationwide uniformity. This study offers a novel approach by systematically analyzing the “Desa Bahagia” system as a pedagogical model for embedding Pancasila ideology into youth leadership training. It provides actionable insights for policymakers to optimize the programme through standardized training modules, equitable resource allocation, and enhanced philosophical understanding of the system’s principles among stakeholders. Improvements in infrastructure, trainer capacity-building, and curriculum alignment are critical to ensure the programme’s scalability and sustainability. These enhancements will strengthen Indonesia’s pipeline of ethically grounded, nationally conscious young leaders.